Association of FLOWERING LOCUS T/TERMINAL FLOWER 1‐like gene FTL2 expression with growth rhythm in Scots pine (Pinus sylvestris). Issue 1 (18th June 2014) - Avia, Komlan; Kärkkäinen, Katri; Lagercrantz, Ulf; Savolainen, Outi
Summary: Understanding the genetic basis of the timing of bud set, an important trait in conifers, is relevant for adaptation and forestry practice. In common garden experiments, both Scots pine ( Pinus sylvestris ) and Norway spruce ( Picea abies ) show a latitudinal cline in the trait. We compared the regulation of their bud set biology by examining the expression of PsFTL2, a Pinus sylvestris homolog to PaFTL2, a FLOWERING LOCUS T/TERMINAL FLOWER 1 ( FT/TFL1 )‐like gene, the expression levels of which have been found previously to be associated with the timing of bud set in Norway spruce. In a common garden study, we analyzed the relationship of bud phenology under natural and artificial photoperiods and the expression of PsFTL2 in a set of Scots pine populations from different latitudes. The expression of PsFTL2 increased in the needles preceding bud set and decreased during bud burst. In the northernmost population, even short night periods were efficient to trigger this expression, which also increased earlier under all photoperiodic regimes compared with the southern populations. Despite the different biology, with few limitations, the two conifers that diverged 140 million yr ago probably share an association of FTL2 with bud set, pointing to a common mechanism for the timing of growth cessation in conifers.